Highly Active and Durable Co-Doped Pt/CCC Cathode Catalyst for Polymer Electrolyte Membrane Fuel Cells. (10th June 2015) - Jung, Wonsuk; Xie, Tianyuan; Kim, Taekeun; Ganesan, Prabhu; Popov, Branko N.
Highlights: Co-doped Pt core–shell type catalyst having 0.75 nm thick Pt shell is synthesized. Co-doped Pt exhibited mass activity of 0.44 A mgPt −1 at 0.9 ViR-free . Co-doped Pt cathode catalyst showed high stability under cycling conditions. Co-doped Pt catalyst showed only 16% power density loss after 30, 000 cycles. The enhanced stability is due to the increase in onset potential for PtO2 formation. Abstract: Cathode catalyst based on Co-doped Pt deposited on carbon composite catalyst (CCC) support with high measured activity and stability under potential cycling conditions for polymer electrolyte membrane (PEM) fuel cells was developed in this study. The catalyst was synthesized through platinum deposition on Co-doped CCC support containing pyridinic-nitrogen active sites followed by controlled heat-treatment. High resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) studies confirmed uniform Pt deposition (Pt/CCC catalyst, dPt = 2 nm) and formation of Co-doped Pt/CCC catalyst (dPt = 5.4 nm) respectively. X-ray energy dispersive spectrometry (XEDS) line-scan studies showed the formation of Co-core Pt-shell type catalyst with a Pt-shell thickness of ∼0.75 nm. At 0.9 ViR-free, the Co-doped Pt/CCC catalyst showed initial mass activity of 0.44 A mgPt −1 and 0.25 A mgPt −1 after 30, 000 potential cycles between 0.6 and 1.0 V corresponding to an overall measured activity loss of 42.8%. The commercial Pt-Co/C showed initial mass activity of 0.38 A mgPt −1 and ∼70% loss of activity after 30, 000 cycles. The enhanced catalytic activity at high potentials and stability of mass activity for the Co-doped Pt/CCC catalyst are attributed to the formation of compressive Pt lattice catalyst due to Co doping. The Co-doped Pt/CCC showed stable open circuit potential close to 1.0 V under H2 -air with an initial power density of 857 mW cm −2 and only 16% loss after 30, 000 cycles. Catalyst durability studies performed between 0.6 and 1.0 V indicated that Co doping increased the onset potential for PtO2 formation close to 1.0 V vs. reversible hydrogen electrode (RHE). The enhanced catalytic activity and stability of Co-doped Pt/CCC catalyst are attributed to (i) higher onset potential for PtO2 formation resulting in less PtO2 formation during potential cycling which alleviates Pt dissolution in the reverse scan (ii) higher stability of CCC used as a support compared with commercially used supports, and (iii) optimized electrochemical properties of the catalyst and the support which result in synergistic effect between pyridinic nitrogen catalytic sites from the Co-doped CCC support and compressive Pt-lattice catalyst.